PEMANFAATAN MINYAK GORENG BEKAS DAN ABU KULIT BUAH KAPUK RANDU (SODA QIE) SEBAGAI BAHAN PEMBUATAN SABUN MANDI ORGANIK BERBASIS TEKNOLOGI RAMAH LINGKUNGAN - Naliawati Prastiya Ningrum; Muhamad Alfin Indra Kusuma; Nur Rokhati (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Capok Randu (Ceiba petandra (L)) Gaerin van Indica (D.C) are most everseen in Indonesia mainly as horticulture in Central Java, with the total areas of95.107,17 ha. Manufacture of capok randu’s ash leather called Soda Qie and itcontains 78%W of potassium. In the other hand, consumption of frying oil inIndonesia is very high and it increases annually, up to 500.000 tons/year. Ex fryingoil produced still contains plenty of free fatty acid and it can be used as raw materialin preparation of soap with soda qie as a source of alkaly by saponification reaction.This experiment aimed to find the optimum operation condition in soap preparationand the its reaction kinetic. This experiment is designed using RSM method (ResponseSurface Methodology) and software Statistica 6. Parameters in this research are exfrying oil volume of 100 ml, soda qie solution concentration of 300 g / 1000 ml, andsaponification reaction time of 60 minutes. Independent variables are the reaction temperature of 30, 60, 90 oC, ratio of soda qie volume : ex frying oil volume 3:1 ; 4:1; 5:1 ml. Optimation is conducted at saponification reaction time variables of 30, 60,90, 120 minutes. Observed responses are amount of Free Fatty Acid (FFA), and freealkali of the product. The optimum operation condition are gained at temperatur of90oC, reactant ratio of 3:1. In the soap product, the number of FFA are 0,80%, andthe number of free alkali are 0,08%, this is fulfill the SII.0005-72. The rate constantgained were 0,068 menit-1.